Reducing switching losses in indirect matrix converter drives: Discontinuous PWM method - Bak, Yeongsu; Lee, Kyo Beum (Journal of Power Electronics, 2018)
This paper presents a discontinuous pulse width modulation (DPWM) method to reduce switching losses in an indirect matrix converter (IMC) drive. The IMC has a number of power semiconductor switches. In other words, it consists of a rectifier stage and an inverter stage for AC/AC power conversion, which are composed of 12 and 6 switching devices, respectively. Therefore, the switching devices of the IMC suffer from high switching losses in the IMC drives. Various topologies to reduce switching losses have been studied by eliminating a number of switches from the rectifier stage. In this study, in contrast to prior research, a DPWM method is presented to reduce the switching losses of the inverter stage. The effectiveness of the proposed method to reduce switching losses in IMC drives is verified by simulations and experimental results.
Keywords: Current source rectifiers; Discontinuous pulse width modulations (DPWM); Indirect matrix converter; Indirect matrix converter (IMC); Number of switches; Power semiconductor switches; Switching loss; Voltage source inverter; Current source rectifier; Discontinuous pulse width modulation; Indirect matrix converter; Switching loss; Voltage source inverter